Estudo anatômico dos estabilizadores mediais da patela - Araújo, Leonardo Heráclio do Carmo (2024)
Patellofemoral joint dysfunction is a common complaint in orthopaedic practice. Among its presentations, patellar dislocation is the most dramatic and could evolve into recurrent instability. In case of recurrent patellar dislocation, surgical approach is indicated, which consists ofrestoring the function of the patella stabilizers and correcting anatomical changes. The set of structures responsible for the lateral stability of the patella, named as the medial patellar stabilizer complex, consists of the medial patellofemoral ligament (MPFL), medial patellotibial ligament (MPTL), medial patellomeniscal ligament (MPMM) and the medial patella retinaculum (MR). Ligament reconstruction, notably of the MPFL, is a fundamental step in surgical treatment. Knowledge of the anatomy of the patella's medial stabilizers is important both for understanding the structural injuriesand for adequate planning and execution of ligament reconstruction. This work aimed to study the anatomy of the medial patellar stabilizers and their relationship with adjacent structures. Anatomical dissection study on 15 knees, six from cadaver donors and nine from suprapatellar amputation: The medial ligament complex was identified in all the dissected knees. The characteristics, morphometry and relationships with adjacent structures were recorded. The medial patellar stabilizer complex, formed by the MPFL, LPTM, LPMM and medial retinaculum, is situated in the anteromedial region of the knee, connecting the patella to the femur and tibia. It is related to ligaments, tendons, muscles, and intraarticular structures. The study of the anatomy of the patellar stabilizers contributed to the identification of relevant aspects for planning and execution of ligament reconstructions in the treatment of patellar instability.